2019
DOI: 10.1002/fsn3.1223
|View full text |Cite
|
Sign up to set email alerts
|

Black rice addition prompted the beer quality by the extrusion as pretreatment

Abstract: Flavor compounds, including total polyphenols, amino acids, and protein, in beer with extruded black rice as adjunct were detected and analyzed. Beer brewing technique has been intensively investigated in the past century. The chase of beer quality, including the color, flavor, foam, nutrition, and functionality, attracted considerable attention. Hence, headspace solid‐phase microextraction in combination with a gas chromatography coupled to mass spectrometry (HS‐SPME‐GC–MS) was used to analyze flavor compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…The rice beer's amino acid contents vary widely with the process and the rice species. Zhang et al (2019) 42 observed proline, alanine, glutamic acid, and valine as the dominant amino acids in the rice beer, and this finding contrasts with the present study. Amino acid contents are the crucial sources of nutrition to yeast.…”
Section: Resultscontrasting
confidence: 99%
“…The rice beer's amino acid contents vary widely with the process and the rice species. Zhang et al (2019) 42 observed proline, alanine, glutamic acid, and valine as the dominant amino acids in the rice beer, and this finding contrasts with the present study. Amino acid contents are the crucial sources of nutrition to yeast.…”
Section: Resultscontrasting
confidence: 99%
“…More recently, research has investigated how the incorporation of extruded adjuncts influences beer brewing. In terms of organoleptic characteristics, a higher number and concentration of aroma compounds have been detected in beers using extruded grains as adjuncts than in those brewed with unextruded adjuncts [15,100,101]. A study published in 2018 shows a higher content of aroma compounds in extruded corn starch beer than in cooked corn starch beer [101].…”
Section: Future Trendsmentioning
confidence: 99%
“…In another study by Zhang et al in 2019, using extruded black rice, novel compounds (nerolidol, geraniol and geranylgeraniol) were detected that were not present in unextruded black rice beers. Therefore, the use of extruded grains can be interesting from a sensory point of view for brewing [15].…”
Section: Future Trendsmentioning
confidence: 99%
See 2 more Smart Citations